Share trading awareness a bibliometic analysis / Muhammad Syafiq Mahidin - Mahidin, Muhammad Syafiq (2022)
This article provides study on bibliometric analysis of share trading awareness. The stock market play as an indicator of economic mirror, which reflect the economic condition of countries. The market participant such as investor and trader in the market plays as an important role in the stock market. It is important to understand the awareness of share trading to determine the awareness level of traders in the stock market. This bibliometric study focuses on publishing trends, countries producing research on share trading awareness, key authors, major contributing organizations, authorship patterns, keywords and articles with the highest citations. Using data from Web of Science Core Collection (WOSCC) database, with 1843 publications in the period of 1991-2021 as at the date of 14 October 2021. As the end of the results, the number of publications increase year by year based on the selected period. This concludes that the level of awareness of share trading is increasing.